2005
DOI: 10.1111/j.1473-6861.2005.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

The lived experiences of clinical educators with implications for their preparation, support and professional development

Abstract: The article reports on research into the lived experience of being and becoming a speech pathology clinical educator, and examines implications for the preparation and professional development of clinical educators. The Lived Experience of Being a Clinical Educator Model offers valuable insights into the nature of the role and the realities of clinical educators' lives. The model comprises six dimensions of being a clinical educator: a sense of self; a sense of relationship with others; a sense of being a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…More effective supervisor training is one mechanism for addressing some of the stresses associated with student supervision and could lead to improved CE experiences. 26 The importance of CI training for effective and positive CE experiences, and of lack of training as a barrier to participation in CE, has been reported elsewhere, 25,26,28,29 but the literature on physiotherapy CE is sparse. In a nursing study, attendees at supervisor training workshops reported a better appreciation for the role of preceptor and a greater understanding of the placement expectations, which gave them confidence for the supervisory process.…”
Section: Discussionmentioning
confidence: 99%
“…More effective supervisor training is one mechanism for addressing some of the stresses associated with student supervision and could lead to improved CE experiences. 26 The importance of CI training for effective and positive CE experiences, and of lack of training as a barrier to participation in CE, has been reported elsewhere, 25,26,28,29 but the literature on physiotherapy CE is sparse. In a nursing study, attendees at supervisor training workshops reported a better appreciation for the role of preceptor and a greater understanding of the placement expectations, which gave them confidence for the supervisory process.…”
Section: Discussionmentioning
confidence: 99%
“…Narrative inquiry, a research technique widely used in the study of teachers' experiences (e.g., Beattie, 1995;Connelly, 1986, 1991) involves examining research participants' stories to identify recurrent themes and concerns and, as in this case, constructing themed stories to represent the collective and varied experiences of clinical educators. Further discussion of the narrative findings of the research is found in Higgs and McAllister (2005) and McAllister (2003).…”
Section: Methodsmentioning
confidence: 95%
“…The author proposed that effective clinical instruction could be promoted by providing clinical faculty with useful educational tools such as a faculty manual with teaching tips and organizational guides . The CIs' knowledge, abilities and personal attributes combined with professional education all contribute to expertise in the teaching role (Higgs & McAllister, 2005). This is crucial for the future development of the nursing profession.…”
Section: Search Methodsmentioning
confidence: 99%